2019
DOI: 10.3390/cancers11030308
|View full text |Cite
|
Sign up to set email alerts
|

The Role of M3 Muscarinic Receptor Ligand-Induced Kinase Signaling in Colon Cancer Progression

Abstract: Despite a reduction in incidence over the past decade, colon cancer remains the second most common cause of cancer death in the United States; recent demographics suggest this disease is now afflicting younger persons. M3 muscarinic receptor (M3R) mRNA and protein are over-expressed in colon cancer, and M3R can be activated by both traditional (e.g., acetylcholine) and non-traditional (e.g., bile acids) muscarinic ligands. In this review, we weigh the data supporting a prominent role for key protein kinases do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…For proof-of-principle, Rosenvinge et al demonstrated that conditioned media from pheochromocytoma cells can stimulate the proliferation of H508 colon cancer cells, an action blocked by pretreating cells with the muscarinic receptor antagonist atropine [ 60 ]. These findings are consistent with the hypothesis that ACh released from the neuroendocrine tumor stimulated swift regrowth of remnant cells after endoscopic resection of the rectal cancer [ 59 , 60 ].…”
Section: Muscarinic Receptor Agonismsupporting
confidence: 91%
See 1 more Smart Citation
“…For proof-of-principle, Rosenvinge et al demonstrated that conditioned media from pheochromocytoma cells can stimulate the proliferation of H508 colon cancer cells, an action blocked by pretreating cells with the muscarinic receptor antagonist atropine [ 60 ]. These findings are consistent with the hypothesis that ACh released from the neuroendocrine tumor stimulated swift regrowth of remnant cells after endoscopic resection of the rectal cancer [ 59 , 60 ].…”
Section: Muscarinic Receptor Agonismsupporting
confidence: 91%
“…These biological phenomena may have clinical consequences. Pheochromocytomas, uncommon neuroendocrine tumors that secrete excess catecholamines, may also produce excess ACh [ 58 , 59 ]. Despite previous endoscopic resection of a small focus of rectal cancer and vigilant surveillance, an elderly man with an unresectable pheochromocytoma experienced rapid recurrence of the rectal adenocarcinoma [ 60 ].…”
Section: Muscarinic Receptor Agonismmentioning
confidence: 99%
“…Muscarinic receptors are comprised of five subtypes, M 1 ‐M 5 , which are encoded in the bladder detrusor muscle cells 10,11 . They are reported to regulate diverse cellular functions, excessive stimulation of which can result in deterioration of many disorders, such as COPD, cognitive impairment, colon cancer 12‐14 . In human lung fibroblasts, Haag et al 15 have found that the muscarinic receptor agonist CCH could significantly increase collagen synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these findings support important roles for M3R expression and activation in the progression of colon neoplasia [67]. M3R and its downstream signaling pathway may be a promising therapeutic target of colon cancer [68].…”
Section: Ach Signaling and Colon Cancermentioning
confidence: 57%